Factors that influence women’s work-life balance - Valdez Bocanegra, Heira Georgina; Aguilar Arredondo, Beatriz Adriana (JÓVENES EN LA CIENCIA, 2024)
This article analyzes the literature on the factors that influence women’s work-life balance, through six dimensions: gratifications, interference of personal and work time, partner and parenting, healthcare, household responsibilities and free time. In terms of remuneration, women give greater weight to the emotional salary than to the economic salary. Working mothers face great challenges in reconciling their time, because at work they have distractions from their personal lives, and vice versa. The gender roles established by society expect that raising children and household chores are their responsibility, regardless of whether they have a paid job. The overload of this "double shift" influences their physical and mental health. Finally, women have little or no free time, which allows them to prioritize their health or to practice a hobby.